Peritoneal Dialysis Utilization Globally and Opportunities in Lower Income Countries - Finkelstein, Fredric; Khan, Qamar (Pakistan Journal of Kidney Diseases, 2021)
There has been an expansion of peritoneal dialysis (PD) utilization globally over the past several years. This has occurred for several reasons. First, there has been a global increase in the number of patients receiving end-stage kidney disease (ESKD) treatment in high income, middle income and low income countries. Second, recent studies have emphasized the reduced cost of PD compared to hemodialysis (HD) if PD supplies can be acquired at a reasonable cost. Thirdly, it is now widely accepted that since PD is much simpler to do than HD (that is, it does not require large amounts of water, complex water treatment systems, electricity, and machinery), the use of PD in low resource countries has certain obvious advantages. Fourthly, it has become clear from experiences in Hong Kong and Thailand that have developed PD First programs (i.e. the government paying for ESKD care only if PD eligible patients start on PD rather than HD) and programs in Mexico (where there has been limited availability of HD centers) that the vast majority of patients with ESKD, even in low resource countries, are able to successfully be cared for with PD. And, importantly, as programs expand in low resource countries and experience is gained, outcomes of PD improve. Lastly, the International Society of Peritoneal Dialysis (ISPD) has developed comprehensive guidelines for the care of PD patients that has resulted in a dramatic improvement in outcomes for PD patients over the last several years.